The Desire Called Utopia: Re-Imagining Collectivity in Moraga and Castillo - Sánchez-pardo González, Esther (Estudios Ingleses de la Universidad Complutense, 2009)
Through a reading of a selection of Cherríe Moraga and Ana Castillo’s texts –Loving in the War Years (1983), The Last Generation (1993), The Mixiquiahuala Letters (1986) and Sapogonia (1990)–, this paper is an attempt to disentangle the complex web of identity, community, home/land and collective and individual histories in their writing. It also aims to reflect upon the role and the unyielding persistence of utopian thinking today. Throughout their work, Moraga and Castillo attempt to articulate an alternative perspective to the male-biased Chicano Nationalist Movement. They look for themselves on the border, between cultures, resisting a privileged aesthetic realm and creating their own, and also resisting the politics of cultural nationalism. Our aim is to establish a dialogue between Moraga’s positing a “Queer Aztlán,” and Castillo’s ideas on the creation of a space or a land (Sapogon), in which people may belong in and feel free to explore the utopian alternatives they offer.